2018
DOI: 10.3390/land7020057
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Land Use and Land Cover Changes and Their Effects on Biodiversity in Central Kalimantan, Indonesia

Abstract: Land use and land cover (LULC) change causes biodiversity decline through loss, alteration, and fragmentation of habitats. There are uncertainties on how LULC will change in the future and the effect of such change on biodiversity. In this paper we applied the Land Change Modeler (LCM) and Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) Scenario Generator tool to develop three spatially explicit LULC future scenarios from 2015 to 2030 in the Pulang Pisau district of Central Kalimantan, Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 32 publications
0
50
0
2
Order By: Relevance
“…Globally, due to historical and policy reasons, there are completely different land-use structures and trends [64][65][66][67][68][69]. Many studies in European countries indicated that the growth of forest land and abandonment of agricultural areas are common issues across Europe, which had a great impact on biodiversity and landscape [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, due to historical and policy reasons, there are completely different land-use structures and trends [64][65][66][67][68][69]. Many studies in European countries indicated that the growth of forest land and abandonment of agricultural areas are common issues across Europe, which had a great impact on biodiversity and landscape [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Overexploitation of biodiversity stems from human population growth and the associated socio-economic development activities, such as expansion of settlements and agriculture within or close to wildlife habitats. This typically results in wildlife habitat degradation, including deforestation [4], changes in land use and land cover [5], fragmentation [6], and, ultimately, deterioration of habitat quality, leading to biodiversity loss [7]. Since high habitat quality is a key determinant of vibrant wildlife populations in any ecosystem [8], its decline reduces the ability of habitats to sustain diverse wildlife resources, resulting in altered species distributions, composition, and population abundance [9,10], and ultimately in loss of wildlife [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Around 28 million ha of Indonesian forest area were cleared and degraded due to poor management under other land uses between 1990 and 2015 (FAO, 2015a, 2015b; FAO, ). There are several intertwined drivers behind such deforestation and land degradation in Indonesia, including agricultural expansion, illegal logging, and forest fires (Koh, Miettinen, Liew, & Ghazoul, ; Sharma et al., ; Tosca et al., ). Comparing total land area, that is, 190.5 million ha, the total amount of degraded land across the Indonesian archipelago is 78 million ha (i.e., 40.98% of total land area) (Figure ), which is huge and alarming (ICCC, ), and delivers limited benefits to human and environment.…”
Section: Introductionmentioning
confidence: 99%